From Chaos to Clarity: Overcoming Reporting Challenges in Mergers and Acquisitions with Scalable Data Solutions - Venkata Penumarthi, (Journal of Computational Analysis and Applications (JoCAAA), 2021)
Mergers and Acquisitions areimportant for organisations sometimes toimprove their business efficiency. Thereare certain scalable data solutions